2005
DOI: 10.1207/s15516709cog0000_31
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Words: Attentional Learning in Form and Meaning

Abstract: Children improve at word learning during the 2nd year of life-sometimes dramatically. This fact has suggested a change in mechanism, from associative learning to a more referential form of learning. This article presents an associative exemplar-based model that accounts for the improvement without a change in mechanism. It provides a unified account of children's growing abilities to (a) learn a new word given only 1 or a few training trials ("fast mapping"); (b) acquire words that differ only slightly in phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
177
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(192 citation statements)
references
References 94 publications
8
177
0
Order By: Relevance
“…In this respect, computational models may prove useful for understanding how the infant is able to reject second names for objects. In associative models of word learning such as the CALLED model (Merriman, 1999) and the LEX model (Regier, 2005), mutual exclusivity is an emergent property of a system where the retrieval of a name for a familiar object competes or interferes with the learning of a new name for the object. Similar forms of competition in learning can be found in phenomena such as blocking (Kamin, 1969) and proactive interference (Underwood, 1957).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, computational models may prove useful for understanding how the infant is able to reject second names for objects. In associative models of word learning such as the CALLED model (Merriman, 1999) and the LEX model (Regier, 2005), mutual exclusivity is an emergent property of a system where the retrieval of a name for a familiar object competes or interferes with the learning of a new name for the object. Similar forms of competition in learning can be found in phenomena such as blocking (Kamin, 1969) and proactive interference (Underwood, 1957).…”
Section: Introductionmentioning
confidence: 99%
“…Liljencrants and Lindblom (15) explored the space of possible vowel systems and found that those with the greatest perceptual contrast corresponded fairly well to vowel systems found in the world's languages. If related ideas can account for universal tendencies in named color categories across languages, then that would suggest a loose parallel between the forces that create categories of sound and those that create categories of meaning (16,17).…”
mentioning
confidence: 99%
“…Consistent with this proposal, several models (e.g., Mayor & Plunkett, 2010;Regier, 2005) have shown how mutual exclusivity might emerge in cue interactions in associative learning. Also consistent with this proposal are studies tracking moment-to-moment eye gaze direction in infants (Halberda, 2009); the attention shifting by infants in these studies resembles those of adults in highlighting experiments .…”
Section: Data)mentioning
confidence: 60%